FLEXIBLE TUBE INSERTION APPARATUS - TEZUKA RYO; TAKAHASHI TAKESHI (2021)
This flexible tube insertion apparatus has: a flexible insertion part having an elongated shape; a rigidity changing mechanism which is provided along the longitudinal direction of the insertion part in a variable-rigidity range corresponding to at least a partial range of the insertion part, and is configured to be able to change the bending rigidity of the variable-rigidity range; and a rigidity control unit configured to be able to control the rigidity changing mechanism to change the insertion shape of the insertion part when the insertion part is inserted in a subject. The rigidity changing mechanism is configured to operate to sequentially increase the bending rigidity of the variable-rigidity range in the directions from the central part of the variable rigidity range to the both end parts thereof in accordance with control by the rigidity control unit. 可挠管插入装置具有：插入部，其构成为具有可挠性及细长形状；刚性可变机构，其在与插入部的至少一部分的范围相当的刚性可变范围内沿着插入部的长度方向设置，并且构成为能够使刚性可变范围的弯曲刚性变化；以及刚性控制部，其构成为能够对刚性可变机构进行用于使插入部被插入于被检体内时的插入形状变化的控制，刚性可变机构